Pathways to Early Science Literacy: Investigating the Different Role of Language and Reading Skills in Science Literacy Among Early Primary School Children - Prastyaningrum, Ihtiari; Nisak, Sayida Khoiratun; Zulfitri; Dewi, Ni Putu Ayu Kartika Sari; Pattiasina, Petrus Jacob (International Journal of Educational Research Excellence (IJERE), 2024)
The purpose of this study is to examine the distinct roles of language and reading skills in science literacy among primary school students through a qualitative approach. Science literacy, defined as an understanding of scientific concepts and processes, and the capacity to apply them in everyday life, is a crucial competency for students in the modern era. This research employed a case study method, with data collection techniques comprising in-depth interviews, classroom observations and document analysis. The findings indicate that language skills play a pivotal role in assisting students in comprehending and communicating scientific concepts in an effective manner. The aforementioned skills encompass an individual's capacity to comprehend and employ scientific terminology, construct sentences with correct grammatical structures, and convey ideas in a clear and logical manner. In contrast, reading abilities are pivotal for students to obtain, comprehend and integrate information from diverse sources, including scientific texts. Well-developed reading abilities facilitate students to understand intricate scientific texts, construct arguments supported by evidence and draw inferences from available data. This research offers insights into the development of language and reading skills holistically, with the aim of improving science literacy among primary school students. It also emphasises the importance of an integrated and comprehensive teaching approach in science education.